Usage and Perceived Side Effects of Personal Protective Measures against Mosquitoes among Current Users in Delhi - Charu Kohli; Rajesh Kumar; G. S. Meena; M. M. Singh; Jyotiranjan Sahoo; G. K. Ingle (Journal of Parasitology Research)
Background. Mosquito-borne diseases constitute an important cause of morbidity and mortality. The use of personal protective measures (PPM) like mats, bednets, screening, repellents, liquid vaporizers, mosquito coils, and so forth has been advocated as an effective tool in control of mosquito-borne diseases, but data about the safety profile of personal protective measures is still scarce. Objective. To study the usage and side effects of personal protective measures against mosquitoes among current users in Delhi. Materials and Methods. A community-based cross-sectional study among 350 adult individuals selected by systematic sampling method. Data was collected using pretested semistructured questionnaire after taking written informed consent. Data was analysed using SPSS version 17. Chi-square/Fisher’s Exact test was used for qualitative variables to find association and P value <0.05 was considered significant. Results. Out of 350 families selected, 210 belonged to rural area and 140 to urban area. Personal protective measures were used by 219 (62.5%) subjects. Liquid vaporizer was the most preferred method (41.4%). Most common perceived side effect of personal protective measures was headache (7.7%). Other perceived side effects were cough (3.2%), sore throat (2.7%), allergy (1.3%), and eye irritation (0.9%) predominantly among coil users. Conclusion. There is a need to have a close watch for side effects of personal protective measures among users. Further research is also needed to develop safe and effective personal protective measures against mosquitoes.